Comparative Multidisciplinary Perspectives on Omnibus Legislation - Bar-Siman-Tov, Ittai (Legisprudence Library, Studies on the Theory and Practice of Legislation, 2021)
XII, 333 p. 18 illus., 8 illus. in color.